The Concept of Divinity in The Mangongkal Holi Tradition in The Batak Toba’s Culture - Quốc Thắng, John Phan; Styawan, Fransiskus Frendy; Simbolon, Paolo Rigo Wilhelmus; Widodo, Agus (Journal of Asian Orientation in Theology, 2025)
Employed within the Batak Toba community, Mangongkal Holi represents a longstanding tradition that continues to be actively practiced. Functioning as a unifying element, this tradition fosters cohesion amongst the geographically dispersed Batak Toba people across Indonesia. Through a combined approach of literature review and interviews, this research delves into the concept of divinity inherent within Mangongkal Holi. The author's meticulous analysis unveils Mangongkal Holi as more than just a ceremonial practice; it serves as a profound expression and reflection of the human connection to the divine. This tradition embodies esteemed values such as reverence and dedication towards the Creator, while simultaneously reinforcing the bonds of fraternity among the Batak people scattered throughout Indonesia.